Enhancing Knowledge and Preventive Behavior Against Tuberculosis Through Family Based Interactive Education in Cihanjuang Rahayu Village, West Bandung - Evelyn Hemme Tambunan; Idauli Simbolon (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2026)
Tuberculosis (TB) remains a major public health concern in Indonesia, where high prevalence rates are often linked to limited community awareness of prevention, transmission, and treatment adherence. This Community Service Program (PkM) aimed to improve knowledge and strengthen preventive behaviors among residents of Cihanjuang Rahayu Village, West Bandung, through an interactive family based educational intervention. A quasi experimental design with pre and post test assessments was applied to 45 high risk participants, including family heads and core household members. Educational sessions focused on TB symptoms, proper cough etiquette, home ventilation, and the implementation of the Family Directly Observed Treatment Short course (F-DOTS) model. Findings revealed significant improvements in knowledge (mean pre test = 58.2; post test = 87.9; p < 0.001) and preventive behavior (mean pre test = 65.1; post test = 90.3; p < 0.001). These outcomes demonstrate the effectiveness of interactive learning strategies such as group discussions, simulations, and family centered case studies in promoting behavioral change. The family based approach was especially valuable, as family members play a pivotal role in supporting treatment compliance and maintaining healthy home environments. The program’s success suggests the need for integrating similar educational initiatives into local primary health center (Puskesmas) outreach to accelerate Indonesia’s TB elimination target by 2030.